Registration of 'Red River Runner' Peanut. Issue 1 (24th October 2012) - Melouk, Hassan A.; Chamberlin, Kelly; Godsey, Chad B.; Damicone, John; Burow, Mark D.; Baring, Michael R.; Simpson, Charles E.; Dashiell, Kenton E.; Payton, Mark
Abstract : 'Red River Runner' (Reg. No. CV‐116, PI 665474) peanut ( Arachis hypogaea L. subsp. hypogaea var. hypogaea ) is a high‐oleic‐oil cultivar with the experimental designation TX994313 that was cooperatively developed and released by the USDA‐ARS, Texas AgriLife Research, and the Oklahoma Agricultural Experiment Station in 2011. Sustainable peanut production in the southwestern United States is driven by the availability of cultivars possessing high oleic fatty‐acid oil content, high yield, and superior grade. The objective of this work was to develop a high‐oleic peanut cultivar with acceptable yield and superior grade potential (near or above 70%) that would increase the peanut producer's profit per hectare. Red River Runner was selected from progenies derived from a three‐way cross between 'Tamrun 96', breeding line TX901639‐3, and 'Sun‐Oleic 95R' and cooperatively tested for several years. Red River Runner has an excellent yield and moderate tolerance to Sclerotinia blight (caused by Sclerotinia minor Jaggar). Red River Runner is similar to the existing high‐oleic runner cultivar 'Tamrun OL07' in many agronomic characteristics such as yield, seed size, and weight. However, Red River Runner was released because it consistently exhibits a higher grade potential than Tamrun OL07 in some locations in Texas (averaging 5.4 points higher) and in most locations in Oklahoma (averaging 4.6 points higher); therefore in those locations, production of Red River Runner will significantly increase the crop value per hectare for peanut growers.